1998
DOI: 10.1093/toxsci/44.2.214
|View full text |Cite
|
Sign up to set email alerts
|

Acute Respiratory Exposure of Human Volunteers to Octamethylcyclotetrasiloxane (D4): Absence of Immunological Effects

Abstract: Humans are exposed to silicones in a number of commercial and consumer products. Some of these silicones, including octamethylcyclotetrasiloxane (D4), are volatile. Therefore, there is a potential for respiratory exposure. A pharmacokinetic analysis of respiratory exposure to D4 is presented in the accompanying paper (M. J. Utell et al., 1998, Toxicol. Sci. 44, 206-213). Possible immune effects of respiratory exposure to D4 are investigated in this paper. Normal volunteers were exposed to 10 ppm D4 or air for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…5−7 In short-term, controlled human exposure studies, no immunotoxic or pro-inflammatory effects of D4 were observed. 8,9 The Government of Canada declared that D4 does not pose a risk to human health but did recommend environmental regulatory measures. 10 D5 is considered to be a persistent and bioaccumulative compound 11 and has been shown to be effectively removed from the atmosphere via phototransformation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…5−7 In short-term, controlled human exposure studies, no immunotoxic or pro-inflammatory effects of D4 were observed. 8,9 The Government of Canada declared that D4 does not pose a risk to human health but did recommend environmental regulatory measures. 10 D5 is considered to be a persistent and bioaccumulative compound 11 and has been shown to be effectively removed from the atmosphere via phototransformation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…If D 4 exposures were repeated in either case at a frequency shorter than the fat half-life, the net result would be accumulation in the fat tissues, because the input would exceed the elimination output. These results were not evident from previous human exposure studies, because the target tissue disposition was not accurately determined (17,18). Utell et al (17) (Table 7 and Figure 6).…”
Section: Discussionmentioning
confidence: 79%
“…The model was first calibrated using previously reported data on tissue distribution in female rats after single and repeated IV administrations of 14 C-D 4 (1). We validated the predicted results in rats and in humans after inhalation exposure using published independent data (12,17,18). We then used the validated model to predict the pharmacokinetics of D 4 as leached from saline-filled breast implants in women.…”
Section: Hoan-my Do Luu and Joseph C Huttermentioning
confidence: 99%
“…The chemical and physical properties of D 4 are well known [17], and the disposition of D 4 following single and multiple inhalation exposure by rats [9] and subcutaneous injection to mice [18] has been reported. However, there is little published data on the biological fate and toxicological effects of D 4 following human exposure [5,15]. Several studies have investigated the dermal absorption of D 4 and other siloxane materials [4,6,[19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%